APPROACHES TO DEVELOPING A STRATEGIC PROGRAM OF COMPANY’S DIGITAL TRANSFORMATION - I. V. Tarasov (Real Economics Publishing House, 2019)
Russian companies are actively involved in the digital transformation. The key technologies and potential effects are defined, a lot of pilots and prototypes are successfully launched. The next logical step is to scale the concept from the level of individual processes to the level of assets, functions, holding companies and the whole enterprise. In the article, two main approaches to the formation of a strategic digital transformation programs are analyzed: an approach based on scaling of digital tools and an approach based on complex processes transformation. Both these approaches are aimed at increasing the level of digital maturity.